The Problems in Implementing Kurikulum Merdeka in English Classrooms - Ildi Kurniawan; Lestary Hamdani; Mei Hardiah, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This study aims to reveal the problems faced by teachers in implementing the Merdeka Curriculum in English classrooms and the problems found by English teachers based on length of teaching and employment status. This study employed mixed methods as the research design. The samples in this study were English teachers who taught in grades 7 and 10 at Sekolah Penggerak batches 1 and 2 in Bengkulu Province. Data collection was conducted using interviews and questionnaires. The questionnaire was made based on Permendikbud Number 16 of 2022 concerning education process standards, which was then validated by experts. The study revealed that the problems English teachers faced in implementing the Merdeka curriculum fell into a fairly difficult category in three aspects: planning, implementing, and assessing the learning process. English teachers most often find problems during the implementation of the learning process, with a percentage of 35% and a weighted mean of 2.48. This could be due to the fact that they are in the switching phase from the 2013 to the Merdeka curriculum, which makes it difficult to adapt to the new curriculum. However, teachers who found fewer problems were those who had taught for more than 10 years and were certified teachers. This might imply that the certification program has had an impact on teachers' quality.